Dietary information for gut endurance sport testing (Digest): exploring the relationship between gut health, sports nutrition knowledge and nutritional practices in elite sport - Kearns, R.; Dooley, J.; Matthews, M.; McNeilly, A. (Sport Sciences for Health, 2025)
Gastrointestinal (GI) complaints are prevalent among athletes and can have a significant impact on performance, particularly in endurance athletes. Possessing greater nutrition knowledge and effectively applying it may play an important role in optimising an athlete`s performance. Despite this, there is a paucity of research regarding GI experiences, sports nutritional knowledge (SNK) and any reciprocal relationship in elite sport. The aim of this study was to design a novel questionnaire to assess the relationship between common GI complaints, GI health, and SNK in elite athletes, sports nutritionists/dietitians and/or coaches in the United Kingdom and Ireland. The study further explored attitudes and practices regarding diet, supplementation, and training practices to gain a comprehensive understanding of potential causative factors to GI distress. This study developed and administered a novel questionnaire, the `Dietary Information for Gut Endurance Sport Testing` (DIGEST) questionnaire to 400 elite athletes and their coaching staff from various sporting backgrounds across the United Kingdom and Ireland. Participant demographics included a balance of genders, a range of ages from 18 to 65 years, and representation from individual and team sports to ensure diverse athletic disciplines were covered. The cross-sectional questionnaire assessed GI complaints, sports nutrition knowledge (SNK), probiotic usage, dietary practices, and exercise workload. Statistical analyses, including chi-square tests and independent sample t tests, were employed to examine associations between these variables, providing insights into the interplay between diet, supplementation, and gastrointestinal health in elite sports settings. Among the 400 participants, 35.5% (n = 142) reported being diagnosed with a GI condition. The most prevalent condition was stomach cramps, affecting 27% (n = 108) of respondents. During physical activities, 213 athletes experienced GI complaints, with 45.5% (n = 97) reporting symptoms pre-exercise and 38.7% (n = 82) post-exercise. Specific sports showed varying levels of GI complaints, with endurance sports such as triathlons and distance running exhibiting higher rates. The study found no significant correlation between SNK scores and GI complaints (p = 0.13), though a substantial number of participants demonstrated suboptimal SNK scores, with athletes averaging 59% and coaches 58%. Sex-based analysis revealed no significant differences in SNK scores, although females tended to score slightly higher in certain sports. GI complaints are prevalent among elite athletes, particularly in endurance sports, with significant symptoms reported both pre- and post-exercise. Despite the lack of a significant relationship between SNK and GI complaints, improving SNK remains essential for overall athlete health and performance. Targeted nutritional education and intervention strategies are needed to manage GI complaints and enhance athlete performance.